Future Nurses: The Interrelation Between Professional Identity and Psychological Training - Toyirovich, Odinayev (Indonesian Journal Publisher, 2025)
This article analyzes the relationship between professional identification and psychological preparation in future nurses. The development of professional identification in future nurses shapes their attitude toward the profession and affects their success in professional activities. Psychological preparation, in turn, helps nurses manage work-related stress, demonstrate empathy toward patients, and develop teamwork skills. This study explores the relationship between professional identity and psychological training in future nurses using a qualitative method based on literature review and theoretical analysis. Findings reveal that strong professional identity enhances responsibility, motivation, and job satisfaction, while psychological training improves stress management, empathy, and teamwork skills. The interrelation between these factors fosters professional growth, emotional resilience, and career success, highlighting the need for integrated educational programs to strengthen both professional identity and psychological readiness in nursing students.